Activity of tannins from Stryphnodendron adstringens on Cryptococcus neoformans: effects on growth, capsule size and pigmentation - Nakamura Celso; de Mello João; Rozental Sonia; Ishida Kelly (BMC, 2009)
Abstract Background Stryphnodendron adstringens (Mart.) Coville, Leguminosae, also known in Brazil as barbatimão, is rich in tannins and many flavan-3-ols and proanthocyanidins such as prodelphinidins and prorobinetinidins. Previous studies have demonstrated several pharmacological properties of tannins from barbatimão, including anti-candidal activity. Methods The antifungal activity of proanthocyanidin polymeric tannins from Stryphnodendron adstringens (subfraction F2.4) was evaluated against three strains of Cryptococcus neoformans with different capsule expressions, using the broth microdilution technique, light microscopy and transmission electron microscopy. The effect of subfraction F2.4 on C. neoformans and melanoma mammalian cells pigmentation was also evaluated. Results Although susceptibility assays revealed MIC values quite similar (between 2.5 and 5.0 μg/ml), analyses of MFC values revealing that the acapsular mutant Cap 67 was more susceptible to be killed by the subfraction F2.4 (MFC = 20 μg/ml) than the two tested capsular strains (T1-444 and ATCC 28957) (MFC > 160 μg/ml). Optical and electron microscopy experiments revealed relevant alterations in cell shape and size in all strains treated with 1 and 2.5 μg/ml of subfraction F2.4. Capsule size of the capsular strains decreased drastically after subfraction F2.4 treatment. In addition, ultrastructural alterations such as cell wall disruption, cytoplasm extraction, mitochondria swelling, increase in the number of cytoplasmic vacuoles and formation of membranous structures in the cytoplasm were also observed in treated yeasts. Incubation with subfraction F2.4 also decreased C. neoformans pigmentation, however, did not interfere in melanization of B16F10 mammalian cells. Conclusion Our data indicate that tannins extracted from S. adstringens interfered with growth, capsule size and pigmentation, all important virulence factors of C. neoformans, and may be considered as a putative candidate for the development of new antifungal agents.